Ese peligroso objeto del deseo: Representaciones de la colombiana en el cine ecuatoriano - León, Christian (2024)
This paper analyze the modes of representation and discursive regimes related to the emergence of the figure of Colombian women in recent Ecuadorian film. Taking as case studies three emblematic fiction films, analyze social processes and cultural representations of gender and nationality converge in building the character of the Colombian femme fatale. Based associated approaches to feminist criticism, gender studies and migration studies, seeks to unravel the social, cultural and sexual present in the construction of the imagínary film through which ídentíties are constructed and otherness.